EFL students’ responses to learning basic reading and writing skills - Syayid Sandi Sukandi; Dian Noviani Syafar (Universitas Syiah Kuala, 2018)
This research presents the responses from Indonesian EFL students to teaching-learning basic reading and writing skills in the context of Indonesian higher education. The 120 respondents, who completed questionnaires, were students enrolled in Writing 1 and Reading 2 courses in the English Education Study Program of the Teachers Academy in West Sumatra [STKIP PGRI Sumatera Barat]. There were four findings from the survey, namely: 1) EFL students preferred studying reading (37%) more than writing (27%), 2) EFL students read about the same amount of literary texts (25%) as they did popular texts (23%) and academic texts (22%), 3) grammar and spelling are the most difficult aspects for EFL students to learn with 33% having difficulty with basic reading skills, and 53% with basic writing skills, and finally 4) EFL students prefer to open a dictionary when they encounter difficult words in reading a text (62%) and do the same when they have difficulties in expressing their thoughts in writing English (38%). These findings show that EFL students have a variety of responses in terms of learning basic reading and writing in EFL English. In addition, the findings show that the tendency of EFL students to prefer reading to writing is relatively high.